Media Education and Digital Literacy - Galán, José Gómez; Lázaro-Pérez, Cristina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Chapter 1. Theoretical Principles of a New Media and Technology Education. Description: Theoretical approach to the problems addressed in the book. Chapter 2. Outside Training of Spanish University Students of Education for the Didactic Application of Cinema: Formal, Non-Formal, and Informal Perspectives.Description: Study on the effect of training on perceptions of the educational potential of cinema in universities as a teaching instrument.Chapter 3. The Development of the Competency of "Cultural Awareness and Expressions" Using Movie-Induced Tourism as a Didactic Resource. Description: Analysis of the role of film tourism in the development of skills in the cultural sphere.Chapter 4. Assessment of Digital Competencies of University Faculty and Their Conditioning Factors: Case Study in a Technological Adoption Context.Description: Ex post facto methodology for the study of the development of digital competences among university teaching staff. Chapter 5. Tourism and ICT. Bibliometric Study on Digital Literacy in Higher Education.Description: Literature review on digital literacy and tourism in universities. Chapter 6. Portuguese Primary and Secondary Education in Times of COVID-19 Pandemic: An Exploratory Study on Teacher Training and Challenges.Description: Exploratory analysis of ICT teacher training in Portuguese primary and secondary education during the COVID-19 pandemic.